(untitled) (Global Journal of Human-Social Science, 2012)
As Little described, learners’ autonomy has been a new term in the field of applied linguistics. It has become one of the objectives of education now. This paper reviews definition and some misunderstanding of learners’ autonomy, and discuss the roles of teachers in autonomy.